2011
DOI: 10.1007/s13595-011-0088-9
|View full text |Cite
|
Sign up to set email alerts
|

Multinomial logit estimation of a diameter growth matrix model of two Mediterranean pine species in Spain

Abstract: Introduction:Understanding diameter growth of the Mediterranean pine species is fundamental for evaluating and making appropriate strategic decisions in forest management. A matrix diameter growth model for two Mediterranean pine forests ecosystems in Spain has been developed. Methods:Multinomial logistic (MNL) regression was employed to estimate the transition probabilities of a matrix growth model. The model combines individual-tree and stand attributes and explores the effects of independent variables and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
(40 reference statements)
1
5
0
1
Order By: Relevance
“…The R for the relationship between the number of trees per hectare and the DBH was negative, which indicated that competition among the trees affected the growth in DBH. This finding is similar to those reported by Luo et al [53], with a negative correlation between the number of trees per hectare and DBH, and similar to Escalante et al [54], in which forest stand simulations under fixed conditions indicated that the probabilities of diameter growth increase with site productivity increase, and decrease with an increase in the stand density index.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The R for the relationship between the number of trees per hectare and the DBH was negative, which indicated that competition among the trees affected the growth in DBH. This finding is similar to those reported by Luo et al [53], with a negative correlation between the number of trees per hectare and DBH, and similar to Escalante et al [54], in which forest stand simulations under fixed conditions indicated that the probabilities of diameter growth increase with site productivity increase, and decrease with an increase in the stand density index.…”
Section: Discussionsupporting
confidence: 92%
“…Since forest growth is affected by many environmental factors, such as topography and soil [52,53], the DBH of trees of the same age may vary considerably in different environments. From the inventory data for forest management planning and design and DEM, this study initially chose eight influencing factors-elevation, slope, slope aspect, thickness of soil layer, humus thickness, age of tree, canopy density, and number of trees per hectare-to analyze the correlation coefficients [54][55][56]. The results (Table 5) show that the six factors (elevation, slope aspect, humus thickness, age of tree, canopy density, and number of trees per hectare) reached a very significant level (p ≤ 0.01), with a relatively large correlation coefficient (r ≥ 0.1) for four factors, namely, the elevation, age of the tree, canopy density, and the number of trees per hectare, which were included in further modeling and prediction by MLR and GRNN.…”
Section: Correlation Analysismentioning
confidence: 99%
“…(Monfort, 2014), un Quercus robur puede duplicar ese grosor (Barrio y Diéguez-Aranda, 2005). El Pinus pinaster puede alcanzar a esa altura y edad los 50 cm (Barrio et al 2006), aunque otros cálculos, también para el Pinus silvestris, rebajan esa cifra (Escalante et al 2011). Según Mackay (1964) a un Quercus robur que a la altura de 1,3 metros tuviera un grosor de 10 ISSN 0211-1608, ISSN Digital: 2530 cm o menos (el 90% en La Draga) se le calcula una edad inferior a los 30 años, con un efecto de madera vieja inapreciable.…”
Section: Precauciones En La Gestión De Una Base De Datos Radiocronolóunclassified
“…To date, only two size-class models have been developed in Spain (Sánchez Orois and Rodríguez Soalleiro, 2002;Escalante et al, 2011), both based on a transition matrix growth model. Also, some of the whole-stand models developed in Spain can be mathematically disaggregated using a diameter distribution function, which provides more detailed information about stand structure and volume (e.g., Río and Montero, 2001;Río et al, 2005;Diéguez-Aranda et al, 2006a;Castedo-Dorado et al, 2007a;Cabanillas, 2010).…”
Section: Modeling Approachesmentioning
confidence: 99%